The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/br.2015.451
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thoracic aortic vasoreactivity by continuous and intermittent exercise in high-fat diet-induced obese rats

Abstract: Abstract. The aim of the present study was to explore the effects of continuous and intermittent exercise on the thoracic aortic vasoreactivity and free radical metabolism in rats fed with a high-fat diet (HD). Sprague-Dawley (SD) rats were randomly divided into four groups (n=8, each group): Conventional diet (CD), HD, HD with continuous exercise (HCE) and HD with intermittent exercise (HIE). HCE rats swam once/day for 90 min; HIE rats performed swimming exercises 3 times/day, 30 min each time with an interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
2
3
0
2
Order By: Relevance
“…Under normal physiological conditions, JAK2 mediates the signal transduction of a variety of cytokines, including erythropoietin, thrombopoietin, granulocyte-macrophage colony stimulating factor and IL-3, thus regulating and promoting cell proliferation (40). The present study showed that naringin also inhibited JAK2 protein expression in AS rat.…”
Section: A B a Bsupporting
confidence: 50%
See 1 more Smart Citation
“…Under normal physiological conditions, JAK2 mediates the signal transduction of a variety of cytokines, including erythropoietin, thrombopoietin, granulocyte-macrophage colony stimulating factor and IL-3, thus regulating and promoting cell proliferation (40). The present study showed that naringin also inhibited JAK2 protein expression in AS rat.…”
Section: A B a Bsupporting
confidence: 50%
“…5). However, treatment with naringin (20,40 and 80 mg/kg) mitigated this increased expression of STAT3 protein in AS mouse (Fig. 5).…”
Section: Effect Of Naringin On Stat3 Protein Expression In As Mousementioning
confidence: 99%
“…HF‐induced obese mice also exhibit enhanced agonist‐induced contraction in rat aorta (Liu et al . ), rat basilar artery (Lima et al . ) and mouse aorta (Mundy et al .…”
Section: Vascular Function In Obesitymentioning
confidence: 99%
“…A disfunção vascular associada à obesidade tem sido amplamente discutida, sendo que o aumento na contração vascular pode ocorrer tanto pela ativação das vias de sinalização envolvidas na contração, quanto por prejuízos relacionados à ativação das vias de relaxamento. Indo ao encontro de trabalhos prévios (Naruse et al, 2006;Chinen et al, 2007;Liu et al, 2015), que mostram os prejuízos no sistema vascular causado pela obesidade, em nosso estudo observamos que a obesidade potencializa a contração vascular, e que tal resposta independe da presença do endotélio, indicando uma possível disfunção no MLV.…”
Section: Discussionunclassified
“…Para avaliação do perfil lipídico, foram determinados os níveis séricos de colesterol total, triglicerídeos e HDL (Lipoproteínas de alta densidade -High density lipoproteins), por métodos enzimáticos(Liu et al, 2015), em amostras de soros obtidas conforme descrito acima. A partir da concentração sérica de triglicerídeos, foram calculadas as concentrações de VLDL (Lipoproteínas de muito baixa densidade -Very low density lipoproteins), utilizando o seguinte cálculo: VLDL (mg/dL)= Triglicerídeos (mg/dL)/5.…”
unclassified